Fifty years of medieval technology and social change
1 online resource.
Keywords: This volume brings together a series of papers at Kalamazoo as well as some contributed papers inspired by the fiftieth anniversary of the publication of Lynn White Jr.'s, Medieval Technology and Social Change (1962), a slim study which catalyzed the study of technology in the Middle Ages in the English-speaking world. While the initial reviews and decades-long fortune of the volume have been varied, it is still in print and remains a touchstone of an idea and a time. The contributors to the volume, therefore, both investigate the book itself and its fate, and look at new research furthering and inspired by White's work. The book opens with an introduction surveying White's career, with a bibliography of his work, as well as some opening thoughts on the study of medieval technology in the last fifty years. Three papers then deal explicitly with the reception and longevity of his work and its impact on medieval studies more generally. Then five papers look at new cast studies areas where White's work and approach has had a particular impact, namely, medieval technology studies and medieval rural/ ecological studies.